IEEE Access Special Section Editorial: Energy Harvesting Technologies for Wearable and Implantable Devices - Hadi Heidari; Mehmet Ozturk; Rami Ghannam; Man-Kay Law; Hamideh Khanbareh; Abdul Halim Miah (IEEE Access, 2021)
Implantable and wearable electronic devices can improve the quality of life as well as the life expectancy of many chronically ill patients, provided that certain biological signs can be accurately monitored. Thanks to advancements in packaging and nanofabrication, it is now possible to embed various microelectronic and micromechanical sensors such as gyroscopes, accelerometers, and image sensors into a small area on a flexible substrate and at a relatively low cost. Furthermore, these devices have been integrated with wireless communication technologies to enable the transmission of both signals and energy. However, to ensure that these devices can truly improve a patient’s quality of life, new preventative, diagnostic, and therapeutic devices that can provide hassle-free, long-term, continuous monitoring will need to be developed, which must rely on novel energy harvesting solutions that are non-obstructive to its wearer. So far, research in the field has focused on materials, new processing techniques, and one-off devices. However, existing progress is not sufficient for future electronic devices to be useful in any new application, and a great demand exists toward scaling up the research toward circuits and systems. Few interesting developments in this direction indicate that special attention should be given toward the design, simulation, and modeling of energy harvesting techniques while keeping system integration and power management in consideration.